Potensi Limbah Hasil Pertanian Padi menjadi Sumber Bioenergi melalui Konsep Biorefineri dengan Pendekatan P-Graph dan Analisis Ekonomi Teknik di Kabupaten Sleman, Yogyakarta: Indonesia - Prawitasari, Diah Ayu (UII, 2025)
Agricultural waste, especially from rice such as straw, husks, and bran, is one of the abundant biomasses in Indonesia, particularly in Sleman Regency, DI Yogyakarta, which is one of the regions with the highest rice productivity. The potential of rice waste can be used as a source of bioenergy using a biorefinery approach. The concept of a biorefinery is the processing of biomass that produces various products and by-products to achieve sustainability. The analysis of the potential of this biomass waste was conducted using p-graph and techno-economics. Based on the optimization analysis with the p-graph, the optimal and maximal solutions were obtained after running the superstructure flow. The optimal solution indicates that the transesterification process of rice bran into biodiesel is more feasible with a profit of 9000 USD/year. For the maximal solution, an economic analysis was conducted because the products generated are more numerous, allowing for the implementation of a biorefinery approach. The results of the techno-economic analysis show that the production of several bioenergy products will fully recoup the initial investment by the 8th year. The IRR value obtained is 21.7%, while the MARR (Minimum Attractive Rate of Return) is 15%, indicating that the investment is viable for funding. Additionally, from an environmental perspective, the use of biomass waste for bioenergy production has a positive impact by reducing greenhouse gas emissions and pollution, as well as enhancing soil fertility through the application of biochar. From a social perspective, community-based bioenergy production can increase income, improve community welfare, enhance bioenergy production, and support energy independence and sustainability.